Extraskeletal Myxoid Chondrosarcoma in a 19-Year-Old Female: A Case Report Highlighting Diagnostic Challenges and Aggressive Clinical Course - Menezes, Ellen Diniz de; Souza, Daniela Cristina dos Santos (Brazilian Journal of Case Reports, 2026)
Extraskeletal Myxoid Chondrosarcoma (EMC) is a rare soft tissue sarcoma, traditionally characterized by an indolent clinical course and occurrence in the fifth or sixth decades of life. Presentation in adolescents is exceptionally rare and often poses significant diagnostic challenges due to its benign-mimicking radiological appearance. A 19-year-old female presented with a painless subcutaneous nodule in the right scapular region. Initial ultrasound (US) misinterpreted the lesion as a sebaceous cyst due to the hypoechoic nature of the myxoid matrix, leading to a one-year diagnostic delay. Following rapid growth and subsequent biopsy, the patient underwent a wide R0 surgical resection. Histopathological analysis revealed high-grade features, including a mitotic index >20/10 HPF and 20% necrosis, within a 20.0 cm surgical specimen. Despite complete resection, the patient developed widespread pulmonary and lymph node metastases within months. Due to the characteristic chemoresistance of EMC, palliative care was initiated, and the patient passed away five months after the definitive diagnosis. This case challenges the traditional "indolent" classification of EMC. The high mitotic activity and extensive necrosis in this young patient represent a high-grade outlier compared to classic cohorts. The diagnostic delay highlights the need to include rare sarcomas in the differential diagnosis of subcutaneous nodules, regardless of age or benign initial imaging. EMC in young patients can exhibit a highly aggressive phenotype with rapid systemic progression. Early diagnostic suspicion and a multidisciplinary approach are crucial for managing this unpredictable and potentially fatal neoplasm.